Zasada odpowiedniego vacatio legis jako część zasady przyzwoitej legislacji – uwagi z perspektywy prawa karnego - Kulik, Marek (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The paper concerns the role of the principle of appropriate vacatio legis in substantive criminal law. The author starts from the role of system principles within branches of law. Next, he indicates the admissibility of deriving specific principles from principles already known. First, the author indicates the role of the principle of decent legislation, and then the role of the principle of appropriate vacatio legis derived from the first principle.